1968
DOI: 10.1161/01.cir.37.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin-Aldosterone System During Chronic Thiazide Therapy of Benign Hypertension

Abstract: Activity of the renin-angiotensin-aldosterone system was investigated in 53 patients with benign essential hypertension treated with thiazides. Following acute (less than 3 weeks) exposure to thiazide, renin activity was increased in peripheral plasma and sensitivity to infused angiotensin was decreased but only when dietary salt was simultaneously restricted. During chronic (more than 2 months) exposure to hydrochlorothiazide, 32 patients with unrestricted salt intake had normal renin activity in peripheral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1968
1968
1981
1981

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Hormone levels were unremarkable before the addition of amiloride or spironolactone despite doses of frusemide up to 160 mg daily. Since previous studies (Espiner et al, 1969;Nicholls et al, 1974) have shown that hyperaldosteronism frequently occurs towards the end of the diuretic phase in oedematous patients receiving frusemide, it appears that 'adaptation' of the reninangiotensin system may occur with maintenance frusemide therapy, similar to that described in hypertensive patients receiving chronic diuretic therapy (Bourgoignie, Catanzaro, and Perry, 1968).…”
Section: Discussionmentioning
confidence: 66%
“…Hormone levels were unremarkable before the addition of amiloride or spironolactone despite doses of frusemide up to 160 mg daily. Since previous studies (Espiner et al, 1969;Nicholls et al, 1974) have shown that hyperaldosteronism frequently occurs towards the end of the diuretic phase in oedematous patients receiving frusemide, it appears that 'adaptation' of the reninangiotensin system may occur with maintenance frusemide therapy, similar to that described in hypertensive patients receiving chronic diuretic therapy (Bourgoignie, Catanzaro, and Perry, 1968).…”
Section: Discussionmentioning
confidence: 66%
“…Treatment with hydrochlorothiazide and tienilic acid for 3 weeks caused a significant rise in PRA (Figure 2) and no substantial decline during prolonged treatment for 48 weeks was observed. However chronic hydrochlorothiazide therapy has been reported to increase renin less than acute administration (Bourgoignie et al, 1968). Similarly a comparative study of shows that the increase in PRA after 14 weeks of metolazone or hydrochlorothiazide treatment was less than after 1 week of diuretic treatment.…”
Section: Time Course Of Pra Changes During Chronic Treatment With Diumentioning
confidence: 98%
“…Compared to the run-in period PRA was significantly (P< 0.01) increased and no decline in PRA was seen during prolonged diuretic treatment for up to 48 weeks. Times (weeks) Figure 1 Changes (mea ± s.e.mean) in plasma renin activity (PRA) during the first 3 weeks of treatment with either a fixed dose of tienilic acid (upper panel) Gross, 1979;Huang et al, 1979;Bourgoignie et al, 1968;, with tienilic acid (Maxwell & Gross, 1979;Huang et al, 1979) or with metolazone (Dornfeld & Kane, 1977) while the degree of stimulation of PRA and the time of course of PRA changes differs from study to study. In the present study using a constant but rather small daily dose of tienilic acid (250 mg) we found a maximal increase in PRA after one week and a levellingoff during the second and third week (Figure 1).…”
Section: Time Course Of Pra Changes During Chronic Treatment With Diumentioning
confidence: 99%
See 1 more Smart Citation
“…The suggestion that concurrent treatment with ,B-adrenoceptor blocking drugs and diuretics will allow suppression of thiazide-induced renin secretion (Stokes, Weber & Thornell, 1974) is probably irrelevant as Bourgoignie, Catanzaro & Perry (1968) have show that the raised plasma renin activity is not evident with long term thiazide therapy.…”
Section: Renin and P-adrenoceptor Blockade-the Mechanism Of The Hypotmentioning
confidence: 99%